Religion and the state a comparative sociology - Barbalet, J. M., 1946-; Possamai, Adam.; Turner, Bryan S. (London ; New York : Anthem Press, 2011)
With a clear statement of the theoretical issues in the debates about secularization and post-secularism, 'Religion and the State: A Comparative Sociology' considers a number of major case studies - from China, Europe, Singapore and South Asia - in order to understand the rise of public religions in the modern state. By distinguishing between political secularization - the separation of state and religion - and social secularization - the transformation of the everyday practice of religion - this volume offers an integrating framework within which to analyze these different societies.
pt. 1. From deprivitization to securitization -- pt. 2. From pietism to consumerism -- pt. 3. Concluding comments.
Proceedings of a workshop held July 17-18, 2009 at the University of Western Sydney, Parramatta Campus.
Includes bibliographical references.
Print version record.
Master record variable field(s) change: 072
Keywords: Religion and state -- Congresses; POLITICAL SCIENCE -- Political Process -- Political Advocacy; Humanities; Religion and beliefs; Religion: general; Religious issues and debates; Religion and politics; Religion and state; SOCIAL SCIENCE / Sociology of Religion; Electronic books; Conference papers and proceedings; Conference papers and proceedings